Analysis of β-lactone formation by clinically observed carbapenemases informs on a novel antibiotic resistance mechanism - Aertker, K; Chan, H; Lohans, C; Schofield, C (American Society for Biochemistry and Molecular Biology, 2020)
An important mechanism of resistance to β-lactam antibiotics is via their β-lactamase–catalyzed hydrolysis. Recent work has shown that, in addition to the established hydrolysis products, the reaction of the class D nucleophilic serine β-lactamases (SBLs) with carbapenems also produces β-lactones. We report studies on the factors determining β-lactone formation by class D SBLs. We show that variations in hydrophobic residues at the active site of class D SBLs (i.e. Trp105, Val120, and Leu158, using OXA-48 numbering) impact on the relative levels of β-lactones and hydrolysis products formed. Some variants, i.e. the OXA-48 V120L and OXA-23 V128L variants, catalyze increased β-lactone formation compared with the WT enzymes. The results of kinetic and product studies reveal that variations of residues other than those directly involved in catalysis, including those arising from clinically observed mutations, can alter the reaction outcome of class D SBL catalysis. NMR studies show that some class D SBL variants catalyze formation of β-lactones from all clinically relevant carbapenems regardless of the presence or absence of a 1β-methyl substituent. Analysis of reported crystal structures for carbapenem-derived acyl-enzyme complexes reveals preferred conformations for hydrolysis and β-lactone formation. The observation of increased β-lactone formation by class D SBL variants, including the clinically observed carbapenemase OXA-48 V120L, supports the proposal that class D SBL-catalyzed rearrangement of β-lactams to β-lactones is important as a resistance mechanism.